Islamic finance for future entrepreneurs : exploring Tunisian Business students' knowledge and potential usage of Islamic financing products / Kammoun Aida and Karray Imen - Karray, Imen (Faculty of Business and Management, 2014)
In Tunisia, especially after the revolution of 14 January 2011, the economy has experienced a recession that has attracted the new government for its resolution. The topic of Islamic finance can participate in the economic recovery by encouraging firm creation by young people and attracting Islamic foreign investors in Tunisia. With the framework of this paper, we seek to understand empirically, from a questionnaire sent to Tunisian students, the point of view of future entrepreneurs towards the financial Islamic products in order to discern at what level these devices are able to ensure the financial requirements of small or medium firms newly created. Firt, many students think that Islamic finance can be a solution to economic actual crisis of the country by developping products that meet the needs of potential investors. So, it will participate in the job creation and unemployment reduction. We find that a high fraction of respondents consider that the decision to contract with an Islamic bank is founded on both cost and religious conviction. Knowledge of Islamic finance principles is also an important factor favoring the use of Islamic products. Finally, it is found that problems faced when using conventional banks can favor the development of Islamic products of financing especially partnership contracts.